Isolation and Characterization of N Fixing Bacteria from Elephant Foot Yam (Amorphophallus paeoniifolius (Dennst.)Nicolson) Growing Regions of South India - Anjanadevi, I P; John, Neetha Soma; K, Susan John; ML, Jeeva; Misra, Rajsekhar (JOURNAL OF ROOT CROPS, 2015)
Isolation and screening of 130 bacteria from the rhizosphere region of elephant foot yam (Amorphophallus) growing area of South India for their ability to fix atmospheric nitrogen ( Kjeldhal technique) resulted in the identification of 62 isolates having varying levels of nitrogen fixing ability in Jensen's nitrogen free medium. The most potent nitrogen fixing isolates were tested for their efficiency to release plant growth promoting substances like indole acetic acid (IAA), ammonia (NH3), hydrogen cyanide (HCN) and catalase enzyme. Morphological and molecular characterization of the two potent bacterial strains led to the identification of them as Bacillus cereus strain ANctcri-1 (HQ286640) and Pseudomonas aeuroginosa ANctcri-11 (JX974833). A study on the effect of various physiological conditions on growth of this potent bacteria revealed their facultative alkaliphilic halo tolerant nature.